Transformasi Administrasi Pendidikan di Era Digital: Tantangan dan Peluang - Mundzir, Moh; Laventia, Feni (CV. Lentera Literasi Indonesia, 2025)
This study aims to provide an in-depth description of the transformation process in educational administration in the digital era, focusing on the challenges faced and the opportunities that can be leveraged by educational institutions. The research adopts a descriptive qualitative approach using a case study method, involving in-depth interviews, participatory observations, and document analysis in schools that have implemented digital administrative systems. The findings reveal that digital transformation in educational administration faces several challenges, including technological infrastructure gaps, low digital literacy among educational personnel, institutional resistance to change, and data security issues. On the other hand, digitalization offers significant opportunities for improving work efficiency, governance transparency, inter-institutional collaboration, human resource capacity building, and data-driven decision-making. Therefore, the success of digital educational administration transformation is highly dependent on the synergy between technological readiness, policy support, and the strengthening of an adaptive culture within the educational environment.